Longitudinally extensive transverse myelitis after Covid-19 vaccination: case report and review of literature - Seyed Farzad Maroufi; Fereshteh Naderi Behdani; Fatemeh Rezania; Samaneh Tanhapour Khotbehsara; Zahra Mirzaasgari (Taylor & Francis Group, 2022)
Mass vaccination has been the main policy to overcome the Covid-19 pandemic. Several vaccines have been approved by the World Health Organization. With growing vaccination, safety concerns and adverse events that need prompt evaluation are also emerging. Herein, we report a case of a healthy woman with longitudinally extensive transverse myelitis after vaccination with the AstraZeneca vaccine. The patient was successfully treated after ruling out all the possible causes.